Law Enforcement for Smoking Drivers in Surakarta - Rachma Putri Dwi Amalia; Marisa Kurnianingsih (Universitas Muhammadiyah Surakarta, 2025)
This study aims to identify law enforcement for motorists who smoke and obstacles faced by the Police as well as obstacles in prosecuting motorists who smoke while driving in Surakarta. The increasing number of motor vehicles in Indonesia, especially in Surakarta, contributes to the ease of daily activities, but also increases traffic violations, including smoking while driving. One of the habits that is still widely found among motorcyclists is the behavior of smoking while driving, even though the potential danger is very large. This behavior not only endangers the rider himself, but also others around. Based on Lawrence M. Friedman's theory, the three elements of the legal system, legal structure, legal substance and legal culture, still face major challenges in their implementation. The method used in this study is an empirical juridical approach that focuses on examining community behavior. The results of the research are expected to contribute to improving law enforcement and traffic safety. Law enforcement against motorists who smoke while driving in the city of Surakarta, focusing on the role of the Police in tackling traffic violations related to smoking habits.